A Case Study On Improving Spare Part Delivery And Distribution Performance - Teh, Wei Wei (2014)
Spare Parts is one of the main profit generators and value added-after sales service, especially for the automobiles companies. Changes in the competitive environment in automobile and spare parts industry has highlight the importance of high on-time delivery and spare part availability performance. Therefore, companies are always seeking for methods and solutions enabling them to provide the best service to customers through the most efficient ways. This case study is based on a research at a Spare Part Centre of a motorcycle assembler company located in Penang, Malaysia.